Visualizing Sufism: studies on graphic representations in Sufi literature (13th to 16th century) - Martini, Giovanni Maria (Islamicate intellectual history, 2023)
"Visualizing Sufism approaches the question of the presence of graphic materials in Islamic mystical literature from a broad and comprehensive perspective. To this goal, an international group of specialists in the field worked on largely manuscript and unpublished sources with the aim of analysing the use of visual elements in the works of some key figures of Islamic mysticism-Ibn al-'Arabi, Ahmad al-Bini, Sa'd al-Din Hamuyeh, al-Sha'rani-, and in intellectual networks-Hurufiyya and Bektashiyya, Shirin Maghribi and his connections. The result is the most extensive collection of specimens of Sufi graphic materials ever brought together and discussed in a single volume. By virtue of the object of study investigated in the chapters of this book, in addition to the history of Sufism, questions are raised that touch upon numerous areas in the field of Islamic Studies, including intellectual history, codicology, and art history. Contributors Elizabeth Alexandrin, Noah Gardiner, Ali Karjoo-Ravary, Evyn Kropf, Giovanni Maria Martini, Orkhan Mir-Kasimov, and Sophie Tyser"--